A Rules-Based Approach for Configuring Chains of Classifiers in Real-Time Stream Mining Systems. (20th July 2009) - Foo, Brian; van der Schaar, Mihaela
Abstract : Networks of classifiers can offer improved accuracy and scalability over single classifiers by utilizing distributed processing resources and analytics. However, they also pose a unique combination of challenges. First, classifiers may be located across different sites that are willing to cooperate to provide services, but are unwilling to reveal proprietary information about their analytics, or are unable to exchange their analytics due to the high transmission overheads involved. Furthermore, processing of voluminous stream data across sites often requires load shedding approaches, which can lead to suboptimal classification performance. Finally, real stream mining systems often exhibit dynamic behavior and thus necessitate frequent reconfiguration of classifier elements to ensure acceptable end-to-end performance and delay under resource constraints. Under such informational constraints, resource constraints, and unpredictable dynamics, utilizing a single, fixed algorithm for reconfiguring classifiers can often lead to poor performance. In this paper, we propose a new optimization framework aimed at developing rules for choosing algorithms to reconfigure the classifier system under such conditions. We provide an adaptive, Markov model-based solution for learning the optimal rule when stream dynamics are initially unknown. Furthermore, we discuss how rules can be decomposed across multiple sites and propose a method for evolving new rules from a set of existing rules. Simulation results are presented for a speech classification system to highlight the advantages of using the rules-based framework to cope with stream dynamics.